Maxillary Expansion - A Comparative Analysis of Rapid, Slow, and Clear Aligner Approaches - Chang, Chien-Yu (Archive of Orofacial Data Science, 2025)
AIM: To compare the effectiveness of rapid maxillary expanders (RMEs), slow maxillary expanders (SMEs), and clear aligners (CAs) for maxillary expansion in children, including an evaluation of natural growth in untreated control groups. METHODS: A systematic literature search was conducted on PubMed, limited to publications within the past 20 years, adhering to PRISMA guidelines. The search focused on maxillary expansion treatments utilising RMEs, SMEs, and CAs in paediatric patients. Following the removal of duplicate entries and application of predefined inclusion and exclusion criteria, 14 studies were selected for final analysis. The primary outcome parameters assessed were the anterior and posterior transverse differences of maxillary dentoalveolar expansion. RESULTS: RME, SME, and CA demonstrated anterior and posterior maxillary expansion, achieving greater expansion than untreated controls. Reported mean differences ranged as follows: RME: 3.0–5.8 mm/2.7–6.6 mm; SME: 2.2–5.4 mm/2.2–6.7 mm; CA: 1.9–3.7 mm/2.0–3.2 mm; control: 0.1–0.9 mm/0.3–0.5 mm. Posterior maxillary expansion was significantly greater in the CA group compared with the other intervention groups. While RME and SME showed superior posterior expansion, CA achieved comparable anterior expansion, potentially attributable to the relatively inflexible central section of the aligners. CONCLUSION: RME, SME, and CA facilitated greater transverse maxillary development than natural growth. These findings support the clinical application of non-surgical expansion appliances during growth phases to enhance transverse maxillary dimensions, offering clinicians a range of options for paediatric maxillary expansion.